Improving Fish Cultivation Skills Through Making Independent Fish Food for Fish Cultivation Group in Parangargo Village - Yus Cholily; Machmud Effendy; Riza Hakim; Beti Suwandayani (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Fish food is one of the factors that play an important role in the growth process of fish. Fish growth can run optimally if the amount of food, food quality and nutritional content are met properly. For this reason, it is necessary to improve fish farming skills through the manufacture of independent fish food for fish cultivators. This activity is carried out based on partner problems, namely the fish cultivator group in Parangargo Village, Wagir District, Malang Regency. This activity uses multiple methods, namely observation, interviews, lectures and discussions. This activity is equipped with indicators of achievement to facilitate evaluation. This activity was carried out in stages in two locations. The first location was carried out in the Edu Park Hall, Faculty of Agriculture and Animal Husbandry, University of Muhammadiyah Malang and the second was carried out in food processing and fish farming, Probolinggo Regency. The result of this activity is an increase in the knowledge (cognitive) aspect of partner communities about self-fooding, which has increased. In addition, participants also experienced an increase in fish fooding management. In terms of skills in processing alternative foods, an increase of 50%, as measured by the active participation of participants in fish food processing practices.